Re-use of abandoned sanitary ware waste as abrasive particles for abrasive jet machine. (2021) - Muthukumaran, N.; Devaraj, P.; Arunkumar, P.; Sekar, T.
Abstract: In recent years, the growth in the machinery industries has emerged to produce the ceramic components which are non-bio degradable wastes. In this paper, the abrasive particles are produced through a rehash of ceramic sanitary ware wastes to machine the glass material in the abrasive jet machining process. Beforehand, computational fluid dynamics (CFD) analysis is performed on the nozzle to evaluate the flow velocity at the corresponding pressure distributions. It results that the velocity of 810 m/s is achieved at the outlet of the nozzle. The nozzle is designed based on the consequent results of flow analysis. Further, the sanitary ware wastes from washbasin urinals, sinks, bathtubs, toilets, etc are collected and renewed to the form of abrasive particles using sieving and segregation processes. The mixing chamber is fabricated and abrasive particles, dry air is made to mix in the mixing chamber. Then mixed particles are made to flow out to the working chamber through the outlet opening. The high jet velocity of the air and abrasive particle mixture has impinged through a convergent nozzle for machining the glass workpiece in the abrasive jet machining process. Moreover, the performance characteristics of abrasive particles in the abrasive jet machining process are evaluated.